EMOTIONAL SUPPRESSION AMONG COACHES AND ITS RELATIONSHIP TO EGO INFLATION AMONG ADVANCED PLAYERS IN SOME VOLLEYBALL CLUBS IN THE NORTHERN REGION - Lecturer. Qutaiba Hadi Mohammed (Proximus Journal Publishing, 2024)
The significance of the current research lies in studying the impact and relationship of coaches' emotional suppression on the variable of ego inflation among advanced volleyball players in the northern region
Keywords: Suppression; Emotional; Volleyball